Ankle sprain bracing solutions and future design consideration for civilian and military use. (1st February 2022) - Zhao Dubuc, Yingjun; Mazzone, Brittney; Yoder, Adam J.; Esposito, Elizabeth Russell; Kang, Tae Hoon; Loh, Kenneth J.; Farrokhi, Shawn
ABSTRACT: Introduction: Ankle sprains are common injuries within the civilian and military populations, with lingering symptoms that include pain, swelling, giving-way, and a high likelihood for recurrence. Numerous bracing systems are available to stabilize the ankle joint following sprains, with new design iterations frequently entering the market. Currently available braces generally include sleeve, lace-up, and stirrup designs. Sleeves provide mild compression and warmth but limited stability for the ankle, while lace-ups and stirrups appear to be more effective at preventing and treating lateral ankle sprains. Areas covered: This review summarizes the use of various brace options in practice. Their major clinical benefits, and limitations are highlighted, followed by an overview of emerging concepts in brace design. Current advancements in biomechanical simulation, multifunctional material fabrication, and wearable, field-deployed devices for human injury surveillance are discussed, providing possibilities for conceiving new design concepts for next-generation smart ankle braces. Expert opinion: Performance of the commercially available braces are limited by their current design concepts. Suggestions on future brace design include: (1) incorporating high-performance materials suitable for extreme environments, (2) leveraging modeling and simulation techniques to predict mechanical support requirements, and (3) implementing adaptive, customizable componentry material to meet the needs of each unique patient.